2017
DOI: 10.4174/astr.2017.93.3.166
|View full text |Cite
|
Sign up to set email alerts
|

Pectoral nerve block (Pecs block) with sedation for breast conserving surgery without general anesthesia

Abstract: Most regional anesthesia in breast surgeries is performed as postoperative pain management under general anesthesia, and not as the primary anesthesia. Regional anesthesia has very few cardiovascular or pulmonary side-effects, as compared with general anesthesia. Pectoral nerve block is a relatively new technique, with fewer complications than other regional anesthesia. We performed Pecs I and Pec II block simultaneously as primary anesthesia under moderate sedation with dexmedetomidine for breast conserving s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 9 publications
0
43
0
Order By: Relevance
“…Since the introduction of PECS II block, several randomized trials have shown its efficacy in reducing postoperative pain and opioid consumption in patients undergoing mastectomy . However, in all these studies RA techniques were always used in association with GA, and there are only a few anecdotal cases reporting the use of PECS blocks as the primary anesthesia in the literature …”
Section: Patients’ Characteristics By Type Of Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of PECS II block, several randomized trials have shown its efficacy in reducing postoperative pain and opioid consumption in patients undergoing mastectomy . However, in all these studies RA techniques were always used in association with GA, and there are only a few anecdotal cases reporting the use of PECS blocks as the primary anesthesia in the literature …”
Section: Patients’ Characteristics By Type Of Surgerymentioning
confidence: 99%
“…Murata et al firstly reported two cases of breast surgery (a simple mastectomy and a lumpectomy) without axillary surgery in two women aged 91 and 94, respectively. Subsequently, in 2017, Moon et al reported a 49‐year‐old woman undergoing WLE + ANC treated successfully with PECS blocks and sedation. Finally, Galán Gutiérrez et al have recently reported two patients with multiple comorbidities, including severe respiratory disease, who received Mx + axillary surgery with a similar anesthetic technique.…”
Section: Patients’ Characteristics By Type Of Surgerymentioning
confidence: 99%
“…In addition to non-narcotic multi-modals, the use of regional anesthesia to control pain in the perioperative period is also being explored. It is known that injuries to muscle and nerves during breast surgery in the acute postoperative period and more severe acute postoperative pain are risk factors for chronic pain [13,14] . A randomized study by Karmakar et al [15] assessed the development of chronic pain after modified radical mastectomy in patients who received thoracic paravertebral block (TPVB) vs. placebo and found that patients who received the TPVB exhibited fewer symptoms and signs of chronic pain [15] .…”
Section: The Role Of Regional Anesthesia In Breast Surgery Casesmentioning
confidence: 99%
“…In a randomized controlled trial by Wahba and Kamal, they compared traditional paravertebral block to pectoral nerve block and found that, among patients undergoing modified radical mastectomy, those who received pectoral block had less morphine consumption and lower intensity of pain in the first 12 h compared to patients who received paravertebral block [22] . Moon et al [13] presented a case in which a pectoral nerve block was used in a patient who underwent monitored anesthesia care, thereby avoiding complications related to general anesthesia. The advantages of the pectoral block include no risk of sympathectomy and less restrictions on use of anticoagulants with studies showing a reduced postoperative morphine consumption in the first 24 h and lower pain scores in the first 12 h in the pectoral block group compared to TPVB in modified radical mastectomy.…”
Section: The Role Of Regional Anesthesia In Breast Surgery Casesmentioning
confidence: 99%
See 1 more Smart Citation